Penggunaan Metode Mind Mapping sebagai Upaya untuk Meningkatkan Kompetensi Writing Teks Descriptive Siswa Pada MTsN Langsa - Fauziatul Halim (At-Tarbawi : Jurnal Pendidikan, Sosial dan Kebudayaan, 2019)
This is evidenced by the results of the study, which showed differences in results, before and after the action was taken. That's why researchers try mind mapping methods to overcome them. This method is quite interesting, because it uses images created by students, which can be colored and decorated as students want and can come up with ideas in writing. The results of observation during the study, showed that students looked enthusiastic once the mind mapping method was introduced to be applied to writing. When doing any task, all can collect tasks. From the results of data processing, the percentage of mastery learning obtained in Cycle I was 39%, in Cycle II it was 100%,. These results indicate an increase in each cycle. Based on these results, the researcher suggests that MTs English teachers try to use the mind mapping method for learning aspects of writing as well as other aspects of learning. Researchers believe that exceptional student creativity will be seen in the results or mind mapping picture. Besides being able to foster creativity and interest, this method also contains various methods and can generate ideas.